"Chagas Express XXI": A new ArtScience social technology for health and science education-A case study in Brazilian endemic areas of Chagas disease with an active search of chronic cases. - Tania C Araujo-Jorge (Public Library of Science (PLoS), 2021)
Background Chagas Disease (CD) affects 6-7 million people worldwide and is related to poverty-promoting conditions. Chronic asymptomatic cases are mostly invisible to health systems. Aiming (1) to translate CD discoveries into education/information practices to raise alertness and empowerment of affected people; and (2) to perform an active search of CD cases, articulating intersectoral actions to improve the access of infected people to the local health service for the treatment of CD; our research group developed and tested under field conditions as innovative social technology: an itinerant education interdisciplinary setting named "Chagas Express XXI" (CE21). Methodology CE21 was created as an "imaginary train" with ~40 ArtScience workshops, games, laboratory activities and conversation circles. An entry/exit plus six activity modules combined associations of affected people, microscopic observations, One Health education, and wellness activities. CE21 was conceived as a social technology, since all the processes were co-created with CD patients and inter-sector local partners. Descriptive statistics showed quantitative data collected throughout the expeditions (CD knowledge, serological results). Qualitative data accessed the public perceptions about the education activities. Principal findings CE21 was exhibited in local educational institutions (schools, universities) in four cities, engaging 2,117 people that evaluated the 41 activities carried out. Citizens and health professionals enjoyed acquisition of information related to blood, parasites, vectors, reservoirs, environmental changes, and social determinants of CD. Further, local legacies of 600 participants volunteer for health promotion groups and CD associations, local empowerment groups to fight for better health conditions, and 05 mural paintings. We observed that 81% of the participants ignored the possibility of treating CD while 52% of the participants requested a blood test for CD showing seropositivity in 20% of them. Conclusions CE21 is a social technology potentially useful for health and science education and active search of asymptomatic CD chronic cases. Moreover, this technology may be adapted to understand and to cooperate in other potentially epidemic situations, especially NTDs related.